2011
DOI: 10.2139/ssrn.1913906
|View full text |Cite
|
Sign up to set email alerts
|

Do Better-Connected CEOs Innovate More?

Abstract: We present evidence suggesting that chief executive officer (CEO) connections facilitate investments in corporate innovation. We find that firms with better-connected CEOs invest more in research and development and receive more and higher quality patents. Further tests suggest that this effect stems from two characteristics of personal networks that alleviate CEO risk aversion in investment decisions. First, personal connections increase the CEO's access to relevant network information, which encourages innov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
31
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 8 publications
3
31
0
Order By: Relevance
“…Sunder, Sunder, and Zhang (2017) report that CEOs with pilot licenses are successful in corporate innovation. Faleye, Kovacs, and Venkateswaran (2014) find that better-connected CEOs invest more in R&D and their firms file more and higher-quality patents. Custodio, Ferreira, and Matos (2019) show that CEOs with general managerial ability spur innovation because they acquire knowledge beyond the firm's current technological domain and are less sensitive to the risk of termination.…”
Section: Introductionmentioning
confidence: 86%
“…Sunder, Sunder, and Zhang (2017) report that CEOs with pilot licenses are successful in corporate innovation. Faleye, Kovacs, and Venkateswaran (2014) find that better-connected CEOs invest more in R&D and their firms file more and higher-quality patents. Custodio, Ferreira, and Matos (2019) show that CEOs with general managerial ability spur innovation because they acquire knowledge beyond the firm's current technological domain and are less sensitive to the risk of termination.…”
Section: Introductionmentioning
confidence: 86%
“…The literature has suggested that the locus of innovation and knowledge circulation lies in dynamic, competency-based business networks (Voss (2003), Walters and Buchanan (2001), and Wright and Burns (1998)). One example is that CEO network connections facilitate corporate innovation (Faleye, Kovacs, and Venkateswaran (2014)). In this regard, there is anecdotal evidence suggesting that foreign institutional investors could facilitate networks among different stakeholders.…”
Section: Knowledge Spilloversmentioning
confidence: 99%
“…Likewise, Faleye, Hoitash, and Hoitash (2011) demonstrate that while monitoring quality improves when a majority of independent directors are very “hands‐on” in their monitoring duties, firms with boards that intensely monitor the management experience less firm innovation. In another study, Faleye, Kovacs, and Venkateswaran (2014) document that firms whose CEOs are better connected through their past employment, education, and social networks receive more and higher quality patents. Likewise, using the social connections between directors and their CEO as a measure of board friendliness, Kang et al.…”
Section: Introductionmentioning
confidence: 99%